Engineering Islets From Stem Cells: The Optimal Solution for the Treatment of Diabetes? - Du, Suya; Li, Yanjiao; Geng, Zhen; Zhang, Qi; Buhler, Leo H.; Gonelle-Gispert, Carmen; Wang, Yi (Frontiers in Immunology, 2022)
Diabetes is a metabolic disease characterized by insulin deficiency. Bioengineering of stem cells with the aim to restore insulin production and glucose regulation has the potential to cure diabetic patients. In this review, we focus on the recent developments for bioengineering of induced pluripotent stem cells (iPSCs), mesenchymal stem cells (MSCs), embryonic stem cells (ESCs), and pancreatic progenitor cells in view of generating insulin producing and glucose regulating cells. This new approach has recently been translated to the clinic and the first type 1 diabetic (T1D) patients have been transplanted with bioengineered embryonic stem cells and have become normoglycemic without receiving exogenous insulin.